Hubungan Dukungan Keluarga Terhadap Mekanisme Koping Pada Pasien Kanker Servik Yang Menjalani Kemoterapi Di Rsud Dr. Moewardi - Sudiyanti, Eni; , Sulastri, S.Kp., M.Kes (2017)
Abstract Background. Treatment of cancer have been developed various kinds of treatment of pharmacological therapy, radiotherapy, chemotherapy, hormonterapi, immunotherapies, even surgery with risks that arise so that patients with cervical cancer requires a systemic approach to the treatment of the disease. Although chemotherapy is often the primary choice alternative for cancer treatment, but chemotherapy have serious side effects. Anxiety experienced by patients undergoing chemotherapy for cervical cancer will respond with actions differently by each patient. Response or individual coping mechanisms to situations that threatened her both physically and psychologically. Purpose. Aim. This study was to determine the relationship of family support for coping mechanisms in patients with cervical cancer who undergo chemotherapy in Hospital Dr. Moerwardi. Method. This research is an analytic (survey) using cross sectional approach. The research sample of 65 patients were determined by accidental sampling technique. The instrument used to record data using questionnaires. Results. The analysis used chi-square test, the value of p = 0.000 (p <0.05), which means that Ha received. Congclusions. From this research shows that there is a relationship between family support for coping mechanisms in patients with cervical cancer who undergo chemotherapy in Hospital Dr. Moewardi. Keywords: cervical cancer patients, anxiety, coping mechanisms